Using Profile Analysis for Assessing Need in Domestic Violence Courts - Scott, Diane L. (American journal of criminal justice, 2007)
This study utilizes profile analysis to evaluate the social and economic justice impacts of domestic violence court processes. Data were gathered from all cases involved in a Domestic Violence Unified Family Court in one Florida county from January 1 through December 31, 2003. Findings suggest domestic violence courts are not responding equitably to victims (petitioners), which means that some petitioners may be revictimized by the system. Furthermore, in cases involving criminal behavior, the court system’s focus on criminality may not be having an impact on reducing the recurrence of domestic violence.